Niewydoloność serca i płuc, transplantologia Oxygen saturation after supplementation through the nasal catheter and 6-minutes walk test as prognostic factors during referral for lung transplantation patient’s with idiopathic pulmonary fibrosis - Jastrzębski, Dariusz; Kozielski, Jerzy; Nowak, Jolanta; Gumola, Anna; Wojarski, Jacek; Zakliczyński, Michał; Poloński, Lech; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2005)
Background: Lung transplantation becomes well known therapeutic methods in treatment patients with nonreversible lung damage due to idiopathic pulmonary fibrosis. An accurate referral patient for lung transplantation is still clinically difficult. Aim: The aim of the study is to identify prognostic factors that would differentiate patients with Idiopathic pulmonary fibrosis (IPF) between those with and without a chance to survive until lung transplantation. Material and methods: A retrospective study was performed in patients IPF referred for lung transplantation between September 1999 and April 2005. Analysis included demographic data, time from referral to transplantation, functional tests (FVC, FEV1, FEV1%VC, PaO2 at rest and after oxygen supplementation), distance walked during 6-min walk test and pathogens in the respiratory tracts. The patients were divided into two groups: group I – lung transplant candidates who survived until successful procedure or are still on waiting list, and group II – lung transplant candidates who died on the waiting list. Results: There was a statistical difference between the two groups in PaO2 after supplementation via a nasal catheter (PaO2 suppl) (p=0.0087) and distance during 6-min walk test (p=0.0018). Conclusions: It appears that simple functional tests of the respiratory system (peripheral blood gas analysis and 6-min walk test) define survival in patients with IPF until lung transplantation.